Peranan Lembaga Bantuan Hukum Cahaya Kebenaran Dan Keadilan (YLBH-CKK) terhadap Masyarakat Miskin yang Mengalami Kasus Pidana di Pengadilan Negeri Kelas I B Kisaran - Julpan Hartono Suria Manja Manurung; Taufik Siregar; Rizkan Zulyandi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this research is to analyze the legal regulations regarding the provision of legal aid in Indonesia, the role of the The Truth and Justice Light Legal Assistance Institution for the poor who experience criminal cases and the constraints they face for the poor who experience criminal cases (Studies at Class IIA District Courts range). The research method used is descriptive method, while the data analysis technique uses qualitative. The results of the research show that the provision of legal assistance to the poor is regulated in Law no. 16 of 2011 concerning Legal Aid. YLBH-CKK provides legal assistance based on requests for legal assistance from residents who have experienced criminal cases. The obstacles faced by YLBH-CKK for the poor are: the public still does not understand the Legal Aid Law by assuming that every transaction with a legal aid institution is synonymous with spending money The big one, there are no restrictions in law who are entitled to legal aid so that criminals who have become recidivists can apply for legal aid, there are advocates who ask for payment from clients receiving legal aid without heeding the applicable rules, weak supervision of advocates when interact with clients, as well as the lack of allocation of funds from the government.